2015
DOI: 10.1089/end.2014.0799
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intrarenal Surgery Versus Percutaneous Nephrolithotomy Versus Extracorporeal Shockwave Lithotripsy for Treatment of Lower Pole Renal Stones: A Meta-Analysis and Systematic Review

Abstract: RIRS offers a relative higher SFR while it has a longer operative time. PCNL is associated with the highest SFR at the expense of the longest hospital stay. SWL is performed as an outpatient procedure with a relative shorter operative time; however, it has lower a SFR and higher re-treatment rate. The categories of complications vary while the overall complication rates are comparable among the three treatment techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 38 publications
1
40
0
4
Order By: Relevance
“…Similar to the literature results, hospital stay was significantly shorter in the RIRS group compared with the PCNL group (p<0.001). [24,28] The limitations of our study are its retrospective nature, small number of patients included, being a single-center study, and a short follow-up time. Because of the retrospective nature of our study, attention was focused on the diameter of the stone.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the literature results, hospital stay was significantly shorter in the RIRS group compared with the PCNL group (p<0.001). [24,28] The limitations of our study are its retrospective nature, small number of patients included, being a single-center study, and a short follow-up time. Because of the retrospective nature of our study, attention was focused on the diameter of the stone.…”
Section: Discussionmentioning
confidence: 98%
“…With regards to the hospital stay, a recently published meta‐analysis showed a significantly shorter hospital stay for patients who underwent RIRS when compared with patients who had PNL for the treatment of renal stones . But, in patients who were treated ‘tubeless’ following PNL, the hospital stay was reduced significantly .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that PCNL techniques ensured a significantly higher stone-free rate but also higher complication rates (p < 0.01) and a larger postoperative decrease in hemoglobin levels (p < 0.00001). In contrast, RIRS led to shorter hospital stay (p < 0.0001) (9). A total of 65 patients with a mean age of 4.31 ± 1.99 years (6 months-7 years) have been included in a flexible URS series by Erkurt et al conducted on pre-school children.…”
Section: Discussionmentioning
confidence: 99%